Forgone, but not Forgotten: Toward a Theory of Forgone Professional Identities - Obodaru, Otilia (Academy of Management Journal, 2017)
Through an inductive, qualitative study, I developed a process model of how people deal with professional identities they have forgone by choice or constraint. I show that, when forgone professional identities are linked to unfulfilled values, people look for ways to enact them and retain them in the self-concept. I further identify three strategies that people use to enact foregone professional identities: (1) real enactment (i.e., enacting the forgone identity through real activities and social interactions either at work or during leisure time), (2) imagined enactment (i.e., enacting the forgone identity through imagined activities and interactions, either in an alternate present or in the future), and (3) vicarious enactment (i.e., enacting the forgone identity by observing and imagining close others enacting it and internalizing these experiences). These findings expand our conceptualization of professional identity beyond identities enacted through activities and interactions that are part of formal work roles, and illuminate the key role of imagination and vicarious experiences in identity construction and maintenance.